Genome sequencing and comparative genomic analysis of bovine mastitis-associated Staphylococcus aureus strains from India - Ramamoorthy Sivakumar; Parameswaran Sree Pranav; Madhavi Annamanedi; S. Chandrapriya; Shrikrishna Isloor; Jeyaprakash Rajendhran; Nagendra R. Hegde (BMC Genomics, 2023)
Abstract Background Bovine mastitis accounts for significant economic losses to the dairy industry worldwide. Staphylococcus aureus is the most common causative agent of bovine mastitis. Investigating the prevalence of virulence factors and antimicrobial resistance would provide insight into the molecular epidemiology of mastitis-associated S. aureus strains. The present study is focused on the whole genome sequencing and comparative genomic analysis of 41 mastitis-associated S. aureus strains isolated from India. Results The results elucidate explicit knowledge of 15 diverse sequence types (STs) and five clonal complexes (CCs). The clonal complexes CC8 and CC97 were found to be the predominant genotypes comprising 21 and 10 isolates, respectively. The mean genome size was 2.7 Mbp with a 32.7% average GC content. The pan-genome of the Indian strains of mastitis-associated S. aureus is almost closed. The genome-wide SNP-based phylogenetic analysis differentiated 41 strains into six major clades. Sixteen different spa types were identified, and eight isolates were untypeable. The cgMLST analysis of all S. aureus genome sequences reported from India revealed that S. aureus strain MUF256, isolated from wound fluids of a diabetic patient, was the common ancestor. Further, we observed that all the Indian mastitis-associated S. aureus isolates belonging to the CC97 are mastitis-associated. We identified 17 different antimicrobial resistance (AMR) genes among these isolates, and all the isolates used in this study were susceptible to methicillin. We also identified 108 virulence-associated genes and discuss their associations with different genotypes. Conclusion This is the first study presenting a comprehensive whole genome analysis of bovine mastitis-associated S. aureus isolates from India. Comparative genomic analysis revealed the genome diversity, major genotypes, antimicrobial resistome, and virulome of clinical and subclinical mastitis-associated S. aureus strains.